Characterization of Water Resources in Transcarpathia - Szuhányi, György (Acta Agraria Debreceniensis, 2005)
Transcarpathia is located in one of the wettest parts of the Ukraine. There are 9429 rivers and creeks in the county with a total length of 19.86 thousand kilometers. The length of 152 rivers exceeds 10 km, 4 exceed 100 km (Tisza, Latorca, Ung and Borsava rivers). The average density of rivers is 1.7 km/km2, which is the highest in the Ukraine. The existing water resources are distributed unevenly in the county. The river with the greatest mass of water is the Tisza. Tisza carries 75% of all existing water resources, the remaining 25% is made up of the water in the river Ung and Latorca. Disregarding the uneven distribution of water resources, 80% of water is used up in the basins of the rivers Ung and Latorca from the water resources of the county, which leads to the overload of rivers.The main sources of water supply in Transcarpathia: subsurface waters – for the population of cities and settlements, surface and subsurface waters – for the industry, surface waters – for irrigation.In the interest of protecting existing water resources, it is required to follow current regulations, detecting and averting contaminating sources and establishing water conservation zones.